The Energy Stored in the Aluminum Nanopowder Irradiated by Electron Beam; Key Engineering Materials; Vol. 685 : High Technology: Research and Applications 2015 (HTRA 2015) - Mostovshchikov A. V. Andrey Vladimirovich; Ilyin A. P. Aleksandr Petrovich; Azanov A. A.; Egorov I. S. Ivan Sergeevich (Discharge and Plasma-Beam Technology, 2016)
Title screen